Oral complaints of denture-wearing elderly people living in two nursing homes in Istanbul, Turkey - (:unkn) unknown (My University, 2012)
AIM: The aim of this study was to observe and determine oral complaints of people aged 55 years or older, living in two nursing homes in Istanbul, Turkey, and their satisfaction with their complete or partial dentures by means of a simple questionnaire. METHODS: Two old people's homes (one public and one private) in the district of Uskudar in Istanbul agreed to take part in this study. All residents who were available were invited to answer a piloted nine-point questionnaire with questions on age, gender, physical problems, eating, and communication, aesthetic denture wearing and psychological problems. The questions were asked in person by one investigator. The resulting data were entered into SPSS version 15. RESULTS: Out of a total of 210 residents, 130 (61.9%) took part in the study, of whom 53% (n=71) of residents were living in the private nursing home and 60% (n=81) were female. One hundred and five (80%) were denture wearers. More than half of the residents (59%, n=79) were over 75 years old. Problems were mostly seen in older ages, especially those over 75 years old, over 60% of whom reported problems for all the variables listed in the questionnaire. Women were more aware of halitosis than men. CONCLUSIONS: The results of this study confirm those of previous studies and suggest that elderly people with dentures, and particularly complete dentures, frequently complain of a wide range of problems including: eating, social interaction and communication and these problems have a detrimental influence on their quality of life.
Keywords: Female; Humans; Middle Aged; Quality of Life; Aged; Turkey; Cross-Sectional Studies; Male; Attitude to Health; Oral Hygiene; Toothbrushing; Denture, Complete; Esthetics, Dental; Age Factors; Patient Satisfaction; Pain Measurement; Sex Factors; Dental Prosthesis, Implant-Supported; Eating; Health Status; Mouth Diseases; Mastication; Interpersonal Relations; Speech; Denture, Partial; Halitosis; Nursing Homes; Private Sector; Public Sector